KEMAMPUAN DARI Lactobacillus plantarum GALUR IS-10506 DAN IS-20506 DALAM MENGHAMBAT AKTIVASI NFkB, MEREGULASI TURUN TNF-RECEPTOR 1 (TNF-R1) DAN OPOPTOSIS PADA BRUSH SEL EPITEL BORDER Rattus novergicus YANG DIINDUKSI LPS - Kusuma, Titis Sari; Riawan, Wibi; Gunadi Ranuh, I Gusti Made Reza; S. Surono, Ingrid (Jurnal Kedokteran Brawijaya, 2008)
Probiotic bacteria have a beneficial effect on diarrhea. In this study, we have examined effect of Lactobacillus plantarum Strain IS-10506 (LIS-10506) and IS-20506  (LIS-20506) on inhibition of NFκB activation, downregulation TNF Receptor-1 (TNF-R1) and Apoptosis in Epithelial Brush Border of Rattus novergicus induced with LPS. On the first day, LPS was inducedto Rattus novergicus per oral. At the 3rdday, Lactobacillus plantarum Strain IS-10506 and LIS20506 separately were supplemented for 7 days (the 3rdday up to the 9thday). Rat was sacrificed after anaesthetizing with ether to assess NFκB activation, TNFR1 and apoptosis. Result showed the decreases of activation NFκB in LIS-10506 group as well as in LIS-20506 group, significantly different, in NFκB activation at group with only LPS (average 14.33+4.509) compared to group with LIS-10506 induction (average 2.00+1.732)and LIS-20506 induction (average 1.33+1.528), at p( p<0.000). Downregulation of TNF-R1 was significant  at LPS group compared to LIS-10506 induction as well as LIS-20506 induction. The index of apoptosis showed significant of degradation (p<0.000) after induced by LIS, where LPS group (14.67+2.517), LIS-10506 induction (6.33+2.309) and LIS-20506 induction (6.00+3.000). As a conclusion, supplementation of LIS-10506 and LIS-20506 separately will inhibit theNFκB activation, and although the mechanism was not sure, what by significant degrade the expression TNF-R1( as ekuivalen of activity TNFα), and the mentioned give the implication that happened by the degradation of occurence apoptosis at cell of epitel bush border intestine.